Netter atlas de neurociencia - Felten, David L.; Netter, Frank H. 1906-1991; Shetty, Anil N. (Barcelona Masson, 2010)
Netter's Atlas of Neuroscience, by David L. Felten and Anil N. Shetty, is an atlas and textbook that combines nearly 400 illustrations and radiologic images highlighting key neuroanatomical concepts and clinical correlations with updated information that reflects our current understanding of the nervous system. It offers user-friendly coverage in three parts-an overview of the nervous system, regional neuroscience, and systemic neuroscience- that enable you to review complex neural structures and systems from different contexts. Online access to Student Consult- where you'll find the complete fully searchable contents of the book, videos of imaging sequences, links to relevant content in other Student Consult titles, and more- further enhances your study and helps to prepare you for exams.
Sección I: Visión general del sistema nervioso. 1. Neuronas y sus propiedades -- 2. Cráneo y meninges -- 3. Encéfalo -- 4. Tronco del encéfalo y cerebelo -- 5. Médula espinal -- 6. Ventrículos y líquido encefalorraquídeo -- 7. Vasculatura -- 8. Neurociencia del desarrollo -- Sección II: Neurociencia regional. 9. Sistema nervioso periférico -- 10. Médula espinal -- 11. Tronco del encéfalo y cerebelo -- 12. Diencéfalo -- 13. Telencéfalo -- Sección III: Neurociencia sistémica: 14. Sistemas sensitivos -- 15. Sistemas motores -- 16. Sistemas autónomo-hipotalámico-límbico
Keywords: Neurociencias -- Atlas; Nervioso, Sistema -- Atlas